Can classical surface plasmon resonance advance via the coupling to other analytical approaches? - Geilfuss, David; Boukherroub, Rabah; Dostalek, Jakub; Knoll, Wolfgang; Masson, Jean-Francois; Baeumner, Antje J.; Szunerits, Sabine (Frontiers in Analytical Science, 2022)
For nearly 40 years, surface plasmon resonance (SPR) analysis has been used to better understand the binding interaction strength between surface immobilized bioreceptors and the analytes of interest. The advantage of SPR, over other affinity sensing approaches such as Western blots and ELISAs approaches, resides in its possibility to reveal binding kinetics in a label-free manner. The concept of SPR has in addition been widely employed for the development of biosensors capitalizing on its direct assay format, short response times, simple sample treatments along with multiplexed sensing possibilities. To this must be added the possibility to reach high sensitivity due to the capability of SPR to detect very small changes in refractive index at the sensing interfaces in particular for analytes of larger size such as cells (e.g., bacteria), proteins, peptides and oligonucleotides. Challenges inherent to all affinity approaches call for further research and include nonspecific surface binding events, mass transportation restrictions, steric hindrance, and the risk of data misinterpretation in case of lack of selective analyte binding. This opinion article is devoted to outlining the different approaches proposed to address these challenges by e.g. coupling with fluorescence read out, electrochemical sensing, mass spectroscopy analysis and more recently to integrate lateral-flow concepts into SPR. Other plasmonic methods such as localized surface plasmon resonance (LSPR), surface enhanced Raman spectroscopy (SERS) will not be considered in detail, as such techniques have nowadays their own standing.